Criminal Justice Systems in Europe. A cross-national quantitative analysis - Becerra-Muñoz, José; García-España, Elisa; Aguilar-Conde, Araceli (My University, 2013)
In the last years, the Crime Observatory of the University of Malaga has analysed police records on criminal activity, has also carried out several crime victims surveys in Spain and has worked on a detailed analysis of the prison system and its connection to the prison policy. This year´s report focuses on the Criminal Justice System, one of the big official data providers, to gather, organize and interpret a great deal of quantitative data from 2000 to 2011. Such longitudinal scrutiny offers data related to public opinion about criminal courts, the quality of criminal justice, its resources, the amount of criminal cases managed on each court, a user´s profile, etc. On this presentation, we´ll concentrate on a comparison of the European countries that constitutes the first chapter of the Report and aims to offer a proper context to the rest of it. Such comparison will explain the national differences in terms of the public budget allocated to courts, legal aid, court fees, incoming criminal cases, length of procedures, clearance rate, as well as homicide, rape, serious assault and robbery convictions, etc. Our aim will be to offer an interesting cross-national analysis of such topics that will provide a reference point from which to debate the national policies related to the Criminal Justice System in the European Countries.
Keywords: Administración de justicia penal; Tribunales penales; Criminal Courts; Criminal Justice Systems; Cross-national analysis; European countries; Quantitative data